jQuery pocket primer - Campesato, Oswald (Dulles, VA : Mercury Learning and Information, 2015)
This book provides an overview of the major aspects, the source code, and tutorial videos to use jQuery. It includes material on jQuery UI Controls, jQueryMobile, HTML5 Technologies with jQuery, and more. It is primarily for self-directed learners who are comfortable with HTML/CSS/Javascript and who also want to learn jQuery. Topics include: integrated coverage of CSS3, jQuery and other important JS toolkits; jQuery Mobile and HTML5 hybrid mobile apps; BackboneJS and Twitter Bootstrap. --
Includes index.
Book is a companied by one computer optical discs entitled' jQuery pocket primer' Bearing the same call number and available at Koleksi Multimedia (level 2,PTSL)
Keywords: JavaScript (Computer program language) -- Handbooks, manuals, etc; Web site development -- Handbooks, manuals, etc; Web sites -- Design -- Handbooks, manuals, etc; Cascading style sheets; HTML (Document markup language)